Global sourcing strategy of electrical and electronics foreign multinationals in Malaysia / Siti Halijjah Shariff, Osman Mohamad and T Ramayah - Shariff, Siti Halijjah; Mohamad, Osman; T, Ramayah (Universiti Teknologi MARA Cawangan Pahang, 2007)
Multinationals will source from within their company (intra) as well as from independent supplier (inter) and these suppliers may be located locally or overseas. This study highlights the percentage of components sourced from intra-domestic, intra-foreign, interdomestic, and inter-foreign sources by electrical and electronic foreign multinationals in Malaysia. These global sourcing strategies were found to be different among the different nationality of the parent company for the electrical and electronic foreign multinationals. However, the dependency on sourcing from parent country or from its subsidiaries in foreign country was not reduced even when the product is at the maturity stage.